100 Exercises to Get You Into Drama School : Improve your acting and audition skills. - Howl, Jona (Methuen drama, 2008)
'The book's main asset is its clarity and accessibility, it relates to its readers in a helpful and clear way.' John Gillett, actor trainer and author of Acting on Impulse. Competition for drama school is fierce, thousands apply every year for only a few places. Preparing well for your audition is key. This book gives drama-school hopefuls the inside track only previously available via professional coaches. It gives clear advice on improving acting skills through effective exercises in which voice, movement, text and character come together with a single aim: to pass that elusive audition and.